Relationship of tissue dimensions and three captive bolt placements on cadaver heads from mature swine (Sus scrofa domesticus) > 200 kg body weight. (8th November 2021) - Anderson, Karly N; Allen, Kaysie J; Baysinger, Angela; Benjamin, Madonna; Berger, Jennifer; Claus, James R; Greco, Brian J; Massie, Emily A; O'Brien, Brett; Ramirez, Alejandro; Rendahl, Aaron K; Reyes, Arquimides A; et al.
Abstract: Three penetrating captive bolt (PCB ) placements were tested on cadaver heads from swine with estimated body weight (BW ) >200 kg (sows = 232.9 ± 4.1 kg; boars = 229.3 ± 2.6 kg). The objectives were to determine tissue depth, cross-sectional brain area, visible brain damage (BD ), regions of BD, and bolt–brain contact; and determine relationships between external head dimensions and tissue depth at each placement. A Jarvis PAS-Type P 0.25R PCB with a Long Stunning Rod Nosepiece Assembly and 3.5 g power loads was used at the following placements on heads from 111 sows and 46 boars after storage at 2 to 4 °C for 62 h before treatment: FRONTAL (F)—3.5 cm superior to the optic orbits at midline, TEMPORAL (T)—at the depression posterior to the lateral canthus of the eye within the plane between the lateral canthus and the base of the ear, or BEHIND EAR (BE)—directly caudal to the pinna of the ear on the same plane as the eyes and targeting the middle of the opposite eye. For sows, the bolt path was in the plane of the brain for 42/42 (100%, 95% confidence interval [CI ]: 91.6% to 100.0%) F heads, 39/40 (97.5%, 95% CI: 86.8% to 99.9%) T heads, and 34/39 (87.5%, 95% CI: 72.6% to 95.7%) BE heads; for the heads that could reliably be assessed for BD damage was detected in 25/26 (96.2%, 95% CI: 80.4% to 99.9%) F heads, 24/35 (68.6%, 95% CI: 50.7% to 83.2%) T heads, and 5/40 (12.5%, 95% CI: 4.2% to 26.8%) BE heads. For boars, the bolt path was in the plane of the brain for 17/17 (100.0%, 95% CI: 80.5% to 100.0%) F heads, 18/18 (100.0%, 95% CI: 81.5% to 100.0%) T heads, and 14/14 (100.0%, 95% CI: 76.8% to 100.0%) BE heads; damage was detected in 11/12 (91.7%, 95% CI: 61.5% to 99.8%) F heads, 2/15 (13.3%, 95% CI: 1.7% to 40.5%) T heads, and 7/14 (50.0%, 95% CI: 23.0% to 77.0%) BE heads. Tissue depth was reported as mean ± standard error followed by 95% one-sided upper reference limit (URL ). For sows, total tissue thickness was different ( P < 0.05) between placements (F: 52.7 ± 1.0 mm, URL: 64.1 mm; T: 69.8 ± 1.4 mm, URL: 83.9 mm; BE: 89.3 ± 1.5 mm, URL: 103.4 mm). In boars, total tissue thickness was different ( P < 0.05) between placements (F: 41.2 ± 2.1 mm, URL: 56.3 mm; T: 73.2 ± 1.5 mm, URL: 83.4 mm; BE: 90.9 ± 3.5 mm, URL: 113.5 mm). For swine > 200 kg BW, F placement may be more effective than T or BE due to less soft tissue thickness, which may reduce concussive force. The brain was within the plane of bolt travel for 100% of F heads with BD for 96.2% and 91.7% of F sow and boar heads, respectively.